Lexical variation in Akokoid (2014)
Language contact among Akokoid, Yoruboid and Edoid has resulted in extensive borrowing from Yoruboid and Edoid to Akokoid. Thus, the speech forms subsumed under Akokoid exhibit lexical items which are similar to Yoruboid and Edoid. To the best of our knowledge, no other scholarly work has addressed the concept ‘lexical variation in these speech forms, hence, the need for this present effort. Twenty lexical items were carefully selected for analysis in this paper. Data were elicited from 34 informants who are competent speakers of Akokoid. Apart from the linguistic data, these informants, including traditional rulers, supplied us with historical facts about the migration patterns of the progenitors of Akokoid. The historical facts coupled with the linguistic data helped us to arrive at the conclusion that some of the words used in contemporary Akokoid found their way into Akokoid as a result of the contact between Akokoid and their neighbours, Yoruboid and Edoid